Edukasi tentang Kepatuhan Minum Obat pada Keluarga Pasien Gangguan Jiwa (Skizofrenia) di Rumah Sakit Jiwa Provinsi Jambi - Yanti, Rahmi Dwi; Putri, Vevi Suryenti (3031-8572, 2024)
Mental disorders (schizophrenia) are complex syndromes that can have devastating effects on sufferers' lives. One of the causes of relapse for people with mental disorders is irregularity in taking medication every day after going home. This community service activity aims to increase patient compliance in taking medication to prevent relapse for people with mental disorders. The educational targets for this service are families and patients with mental disorders at the Jambi Province Mental Hospital polyclinic, totaling 14 people. This service was carried out at the Jambi Province RSJD Polyclinic from March to August 2023. The methods used in this community service activity were lectures and discussions. The media used is leaflets. Questionnaires were given pre-test and post-test regarding medication adherence. The pre-test and post-test results showed that family knowledge about medication adherence increased from 53.1% to 61.2%.